Alzheimer’s Disease: An Overview of Recent Developments and a Look to the Future - Uflacker, Alice (Focus (Am Psychiatr Publ), 2017)
Alzheimer’s disease is a major public health concern, affecting an estimated 40 million people worldwide. Over the past few years, several new diagnostic tests and new diagnostic nomenclatures have emerged, and more than 70 disease-modifying agents are in clinical trials. Naturalistic studies that include biomarkers—such as genomics, metabolomics, and imaging—have yielded additional insights into disease mechanisms and timelines of preclinical disease onset. This article reviews recent developments in epidemiology, diagnostic criteria, and diagnostic tests; provides updates on symptomatic therapies, ongoing prevention trials, and neuropsychiatric symptom treatment options; and ends with a discussion on prospects for a cure.